Functional outcome of debridement, antibiotics and implant retention in periprosthetic joint infection involving the hip: a case–control study. (May 2017) - Grammatopoulos, G.; Bolduc, M-E.; Atkins, B. L.; Kendrick, B. J. L.; McLardy-Smith, P.; Murray, D. W.; Gundle, R.; Taylor, A. H.
Abstract : Aims: Advocates of debridement, antibiotics and implant retention (DAIR) in hip periprosthetic joint infection (PJI) argue that a procedure not disturbing a sound prosthesis-bone interface is likely to lead to better survival and functional outcome compared with revision. This case-control study aims were to compare outcome of DAIRs for infected primary total hip arthroplasty (THA) with outcomes following primary THA and two-stage revision of infected primary THAs. Patients and Methods: We retrospectively reviewed all DAIRs, performed for confirmed infected primary hip arthropasty (n = 82) at out institution, between 1997 and 2013. Data recorded included full patient information and type of surgery. Outcome measures included complications, mortality, implant survivorship and functional outcome. Outcome was compared with two control groups matched for gender and age; a cohort of primary THAs (n = 120) and a cohort of two-stage revisions for infection (n = 66). Results: Mean age at DAIR was 69 years (33 to 87) and mean follow-up was eight years (2 to 17; standard deviation (sd) 5). A total of 52 (63%) of DAIRs were for early PJI (less than six weeks). Greater success in the eradication of infection with DAIR was identified with early PJI, comprising an interval less than a week between onset of symptoms and exchange of modular components with the DAIR procedure. Eradication of infection, complications and re-operation rates were similar in the DAIR and two-stage revision groups. For hips with successful eradication of infection with DAIR, the five-year survival (98%; 95% confidence interval (CI) 94 to 100) was similar to the primary THA group (98%; 95% CI 95 to 100) (n = 43; p = 0.3). The DAIR group had inferior mean Oxford Hip Scores (OHS) (38; 12 to 48) compared with the primary THA group (42; 15 to 48) (p = 0.02) but a significantly better mean OHS compared with the two-stage revision group (31; 0 to 48) (p = 0.008). Patients who required only one DAIR for eradication of infection had a similar mean OHS (41; 20 to 48) to the primary THA group (p = 0.2). Conclusion: The DAIR procedure is associated with a similar complication rate and ability to eradicate infection as two-stage revision. This study emphasises the need for exchange of modular components for improved chances of eradication of infection. This is the first study showing that DAIR is better than a two-stage revision regarding functional outcome. Cite this article: Bone Joint J 2017;99-B:614–22.